Własność intelektualna w kontekście funkcjonowania uczelni wyższej w Polsce (część 1) - Narożna, Dominika (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
Polish higher education institutions are facing the task of managing issues of intellectual property protection. This task is imposed on them by law in Article 86 c of the Law of March 18, 2011 on the amendment to the Law on higher education, the Act on academic degrees and titles and degrees and degrees and titles in art and some other acts. The topicality of this issue has encouraged the author of the paper to discuss copyright, plagiarism and to indicate certain manners of using academic works.